Characterizing implementation strategies using a systems engineering survey and interview tool: a comparison across 10 prevention programs for drug abuse and HIV sexual risk behavior. (December 2015) - Czaja, Sara; Valente, Thomas; Nair, Sankaran; Villamar, Juan; Brown, C.
Abstract Background Although many behavioral interventions have proven to be efficacious, new methodologies are required beyond efficacy trials to understand how to adopt, implement with fidelity, and sustain behavioral interventions in community settings. In this paper, we present a new approach, based on systems engineering concepts and methods, for characterizing implementation strategies that are used to deliver evidence-based behavioral interventions in health and social service settings. We demonstrate the use of this approach with implementation strategies, used or being used for broader dissemination of 10 evidence-based prevention program projects focused on the prevention of drug or HIV sex risk behaviors. Results The results indicate that there are wide variations in intervention approaches and that there are challenges in program implementation including maintaining program fidelity, serving community needs, and adequate resources. The results also indicate that implementation requires a committed partnership between the program developers, implementation researchers, and community partners. In addition, there is a need for adaptability within programs to meet community needs, resources, and priorities while maintaining program fidelity. Conclusions Our methodological approach enabled us to highlight challenges associated with the community implementation of health risk prevention interventions. We also demonstrate how comprehensive descriptions of interventions facilitate understanding of the requirements of program implementation and decisions about the feasibility of implementing a program in community settings.